Proceedings of the 8th International Conference on Pervasive Computing Technologies for Healthcare 2014
DOI: 10.4108/icst.pervasivehealth.2014.255070
|View full text |Cite
|
Sign up to set email alerts
|

PopTherapy: Coping with Stress through Pop-Culture

Abstract: Stress is considered to be a modern day "global epidemic"; so given the widespread nature of this problem, it would be beneficial if solutions that help people to learn how to cope better with stress were scalable beyond what individual or group therapies can provide today. Therefore, in this work, we study the potential of smart-phones as a pervasive medium to provide "crowd therapy". The work melds two novel contributions: first, a microintervention authoring process that focuses on repurposing popular web a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 29 publications
5
111
0
Order By: Relevance
“…Additionally, it is non-trivial to choose when and how to display feedback. Biofeedback displays in the form of games have been found to help reduce stress levels more quickly [10], but representations matter: displaying someone's stress data does make them more aware of their stress levels, but can also exacerbate their stress [33].…”
Section: Self-tracking In Mental Health Contextsmentioning
confidence: 99%
“…Additionally, it is non-trivial to choose when and how to display feedback. Biofeedback displays in the form of games have been found to help reduce stress levels more quickly [10], but representations matter: displaying someone's stress data does make them more aware of their stress levels, but can also exacerbate their stress [33].…”
Section: Self-tracking In Mental Health Contextsmentioning
confidence: 99%
“…This could be integrated into existing computerized mental-health interventions developed by the HCI community [19] to help reduce chronic stress by pre-emptively directing users through psychologically positive environments.…”
Section: Applications Of Enviropulsementioning
confidence: 99%
“…In human-computer interaction (HCI), the importance of identifying and alleviating stress has been recognized, and various different sensing and mobile intervention technologies have been developed to combat the "stress epidemic" [19]. The field of affective computing has already demonstrated that technology can be used to detect and respond to emotional states [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few of these systems explicitly discuss, or design for, the development of social and emotional skills needed for achieving emotional wellbeing (for exceptions see [7,8,9,11]). As such we believe that the potential of digital technology to directly scaffold or promote such learning is currently under-researched.…”
Section: Introductionmentioning
confidence: 99%